Grading in Secondary Schools in Germany – The Impact of Social Origin and Gender - Michael Bayer; Sabine Zinn; Christin Rüdiger (International Journal of Educational Research Open, 2021)
In the German school system, grades are the essential means of performance feedback and assignment. However, little research has been conducted on the factors that determine grades in addition to competencies, and existing findings are poorly replicated. Using data from the representative IQB Trends in Student Performance 2015 survey, our analysis combined a variety of personal and structural characteristics to examine and replicate grade- determining factors in German. In data analysis, we paid particular attention to the data generation processes. The results are interpreted based on Bourdieu's considerations of habitus and status maintenance and Boudon's primary and secondary effects of social origin. The results tie in with the reproduction-theoretical considerations of Bourdieu and Boudon and illustrate the dependence of grades on students' background characteristics.
Keywords: 330; Grading; Teacher effects; Inequality; Social backgroubd